Feeder Transportation Route Evaluation based on Origin-Destination Analysis and Land Function (Case Study of Trans Semarang Feeder 1A, Indonesia) - Khosy, Hadyan Al-Muhith; Setiadji, Bagus Hario; Narendra, Alfa (Civil Engineering Dimension, 2026)
The Route modification for the Trans Semarang feeder line 1 resulted in the creation of feeder line 1A. To evaluate the effectiveness of this change in addressing critical community needs, an analysis was conducted. This study utilized passenger boarding and alighting data obtained through origin-destination surveys, combined with land use data from the Google Earth application. Findings revealed inconsistencies and fluctuations when comparing passenger movement patterns with land use values. The feeder transportation function was deemed effective, with the highest proportion of passengers (23.53%) boarding at the transit shelter. Conversely, the segment between Jalan Perkebunan and Desa Ngadirgo shelters exhibited the lowest passenger volume, attributed to long distances between shelters, extensive forested and plantation areas, and a one-way route. These factors suggest potential benefits of rerouting. Further research is recommended to comprehensively evaluate the broader implications of such modifications.